Screening of lupeol, mangiferin and β-carotene contents in pulp of mango (Mangifera indica L.) varieties at edible ripe stage (Indian Journal of Traditional Knowledge (IJTK), 2023)
Mango fruits are an amazing source of numerous bioactive phytonutrients like lupeol (a novel anti-inflammatory and anticancer dietary triterpene), mangiferin (an antidiabetic, anti-HIV, anticancer, immunomodulatory and anti-inflammatory agent) and β-carotene (a significant carotenoid that functions as a precursor to vitamin A, the conscientious reason for our vision). In the present study, ripe pulp of 23 mango varieties was examined for their contents of lupeol, mangiferin and β-carotene using high performance liquid chromatography-photodiode array detector (HPLC-PAD). Mulgoa had the highest lupeol concentration, measuring 42.52 µg/g and Langra stands second with 36.33 µg/g followed by Pairi (33.56 µg/g), Sensation (28.69 µg/g) and Dashehari with 28.22 µg/g. Mangiferin content was highest in variety Arunika (49.58 µg/g) followed by Ambika (34.80 µg/g), Dashehari (33.31 µg/g), Sensation (29.66 µg/g) and Neelum (27.93 µg/g). Sensation's mature pulp has the highest quantity of β-carotene (109.58 µg/g), followed by Kesar (96.87 µg/g), Dashehari (82.13 µg/g), Mulgoa (79.99 µg/g), Arunika (74.26 µg/g), and Amrapali (70.12 µg/g). The pulp of Dashehari, Sensation, Mulgoa, Arunika, Kesar and Amrapali possessed good to moderate amount of these nutraceuticals and are beneficial for consumption at ripe stage. This study has showed the importance of nutraceutical components present in mango; meanwhile it also encourages mango growers to grow these varieties for better profitability.